Avtoimunske bolezni kože - Anžlovar, Alja (Placebo, 2022)
Being the largest organ in the human body, skin is a common target of autoimmune diseases. In general, autoimmune diseases of the skin can develop as localized autoimmune disorders, which are limited only to the skin, or they can be a part of a systemic autoimmune disease. The first category comprises of bullous skin diseases, which are characterized by the formation of blisters or bullae on the skin as a direct consequence of loss of immunotolerance. In addition to bullous skin diseases, other skin-specific autoimmune diseases include psoriasis, alopecia areata and vitiligo. This article describes the different skin-specific autoimmune diseases, the diverse mechanisms of their development, and avaliable treatment options.
Keywords: alopecia areata; alopecija areata; autoimmune skin disease; Avtoimunske bolezni; avtoimunske bolezni kože; bullous skin diseases; bulozna kožna obolenja; Koža; psoriasis; Psoriaza; vitiligo